Mapping Innovation Paths: A Systematic Analysis of Innovative Work Behavior in Hospitality Industry - Suliati, Ni Nyoman; Noermijati, Noermijati; Sudiro, Achmad; Kurniawati, Desi Tri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
The hospitality industry depends on employees’ innovative work behavior (IWB) to remain competitive, yet prior studies offer fragmented insights into its drivers, dimensions, benefits, and challenges. This study conducts a systematic review of 64 articles (2019–2024) from Scopus and Web of Science using the PRISMA approach. Results show that organizational support, creativity, leadership styles, knowledge sharing, and motivation foster IWB in hotels, with dimensions covering idea generation, promotion, development, and implementation. IWB enhances performance, customer satisfaction, and competitiveness but faces challenges such as limited resources, leadership constraints, and high turnover. This study integrates recent evidence to provide a comprehensive understanding of IWB and practical implications for managers, policymakers, and researchers.